Penerapan Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik Terkait Praktik Manipulasi Data (Fake Account) di Sosial Media Instagram - M. Rizal Ramadhan; Herliani Herliani; Agnes Hernitiana; Veni Kristin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid development of technology encourages the change in crime patterns from conventional to digital through the use of electronic devices. This phenomenon makes many individuals and groups use technology not only for positive purposes, but also to gain financial gain illegally. Instagram as one of the most popular social media applications has also become a space for digital crime practices, especially through the creation of fake accounts. Fake accounts are used for various harmful acts such as online fraud, the spread of fake news, the use of identities or photos without permission, acts of bullying and negative comments that trigger conflicts, to the spread of pornographic content. This research aims to identify the forms of fake account practices on Instagram, analyze the causative factors, and evaluate the application of applicable laws, especially Law Number 19 of 2016 concerning Information and Electronic Transactions. The research method used is empirical legal research with a qualitative approach. The data was collected through interviews with investigators from the Directorate of Criminal Investigation of the Metro Jaya Police, academics, and civil society organizations (CSO). The results of the study show that the practice of fake accounts still often occurs due to low digital literacy, weak supervision from platforms, and not optimal law enforcement. Although Article 35 jo Article 51 paragraph (1) of the ITE Law has regulated the prohibition of data and identity manipulation, its implementation still faces a number of obstacles from aspects of legal substance, enforcement structure, and community legal culture. This study recommends the need for collaboration between the government and social media platforms in limiting the creation of fake accounts, improving people's digital literacy, and reformulating legal rules that are clearer and more adaptive to the dynamics of digital crime. These efforts are needed so that the protection of social media users is optimal and able to create a safe digital space.